Structuring Discretion Among Belgium’s Prison Leave Decision-makers - Robert, Luc (European journal on criminal policy and research, 2020)
Prison leave decision-making remains largely unknown, operating as a black box in which applications enter and decisions come out, without knowing what happens in between. Prison leave decision-making in Belgium is no exception to this. After a prisoner submits an application for prison leave, the prison director has to provide a written opinion about it, which is then sent on to the Service for the Management of Imprisonment (SMI), which decides whether a prisoner should obtain prison leave. Five years after implementing the legislation, the Directorate General of Penitentiary Institutions mandated a national study of prison leave decision-making practices. The study showed that both key actors, prison directors and the SMI, used their own highly discretionary approach to decision-making. There was little transparency regarding the other actor’s approach, fuelling mutual misunderstanding and frustrations about the other actor’s decisions. Since then, attempts have been made to structure discretionary decision-making. In this article, we first outline the types of prison leave as they have come into existence since 2006. Next, key observations of the first national study are given, as they set the scene for what came afterwards. We then go on to reconstruct steps in an ongoing process of structuring discretionary decision-making. These have led to an increased proportion of prison leaves being granted, with more concordance in decision-making between prison directors and staff at the SMI. We conclude the article by linking the Belgian practice to wider debates about decision-making.